Impact Sugar Type, Fermentation Duration, and Concentration of Eco-Enzyme on pH, TDS, and Antibacterial Activity - Primarista, Ni Putu Vidya; Birhi, Damiana Nofita; Abi, Faustina De Yesu Prisila; Titani, Fena Retyo; Wiranata, Arya; Wali, Abdul Rohman (Jurnal Biologi Tropis, 2026)
Eco-enzymes produced from fruit and vegetable waste are increasingly used for waste valorization and natural disinfection, but the combined effects of sugar type, fermentation duration and dilution on their quality remain unclear. This study examined eco-enzymes from mixed fruit peels prepared with granulated sugar, brown sugar and molasses, fermented for 1, 2 and 3 months, and diluted to 20%, 10%, 1%, 0.2% and 0.1%. Physicochemical properties (pH, TDS) and antibacterial activity against Staphylococcus aureus and Escherichia coli were measured; data were analysed by one-way ANOVA with Tukey’s test and Pearson correlation. Eco-enzymes were strongly acidic (≈3.5–3.9) at 20–10% and approached neutrality at 0.1%, with molasses-based formulations maintaining the lowest pH at high dilutions. TDS showed fermentation‑time‑dependent trends that differed between concentrated and dilute solutions. No inhibition was observed in month 1; activity appeared after ≥2 months and was highest at 3 months, with three‑month molasses eco-enzymes at 20% giving the largest inhibition zones and retaining activity at 0.1–0.2%. These findings identify molasses and extended fermentation as key levers to improve eco-enzyme performance as low-cost natural antibacterial agents.